Enlargement of the Optic Chiasm: A Novel Imaging Finding in Glutaric Aciduria Type 1 - Ntorkou, A.A.; Daire, J.; Renaldo, F.; Doummar, D.; Alison, M.; Schiff, M.; Elmaleh-Bergès, M. (American Journal of Neuroradiology, 2021)
SUMMARY: Patients with glutaric aciduria type 1, without early diagnosis and initiation of preventive treatment, often develop movement disorders and various degrees of motor disability due to striatal area–specific damage induced by an acute episode of metabolic decompensation. The neuroimaging phenotype of patients with glutaric aciduria type 1 includes characteristic cyst-like bilateral enlargement of the Sylvian fissures and anterior subarachnoid spaces and signal abnormalities including supratentorial white matter and deep gray matter structure T2 hyperintensities, frequently associated with restricted diffusion. In this retrospective study, we add to the neuroimaging spectrum of glutaric aciduria type 1, a novel imaging finding present regardless of a previous metabolic crisis: the enlargement of the optic chiasm associated with signal abnormalities in the anterior intracranial visual structures observed in 6 of 10 patients. These optic pathway abnormalities are suggested as useful diagnostic clues for glutaric aciduria type 1, and possible pathophysiologic mechanisms are discussed.GA-1glutaric aciduria type 1